STATISTICAL CONVERGENCE FOR GENERAL BETA OPERATORS - Deo, Naokant; Ozarslan, Mehmet Ali; Bhardwaj, Neha (Kangwon-Kyungki Mathematical Soc, 2014)
In this paper, we consider general Beta operators, which is a general sequence of integral type operators including Beta function. We study the King type Beta operators which preserves the third test function x(2). We obtain some approximation properties, which include rate of convergence and statistical convergence. Finally, we show how to reach best estimation by these operators.
Keywords: Beta operators; rate of convergence; statistical convergence